Trial of Methylphenidate and Thioridazine - J Gordon Millichap (Pediatric Neurology Briefs, 1991)
A double-blind, placebo-controlled, cross-over study of methylphenidate (0.4 mg/kg/day) and thioridazine (1.75 mg/kg/day) in 27 intellectually subaverage children is reported from The Nisonger Center for Mental Retardation and Developmental Disabilities, Ohio State Univ., Columbus, OH, and the University of Aukland, New Zealand.